Globalisierung und Integrales Bewusstsein Der Beitrag Jean Gebsers zu einer neuen Weltsicht - Leopold, Heinrich (Novalis Verlag, 2008)
Heinrich Leopold´s study of the relationship between globalisation and integral thinking forges a link between Jean Gebser´s structural model of intellectual thought and current arenas of globalisation. It takes a carefully chosen approach to analysing various forms of globalisation from the point of view of social and individual consicousness. Jean Gebser´s philosophy, which owes much to a world view informed by far eastern philosophy, describes the history of human pereption in terms of a sequence of qualitatively different structures and demonstrates the emergence of a new structure of perception, which he describes as integral. This approach enables Heinrich Leopold to take into account the relevant in-depth analyses of globalisation while at the same time highlightning the divergent attitudes of those who welcome it as well as of those who condemn it, and offering of both. Irrespective of the extent to which globalisation has taken hold and no matter how much the western world have benefited from its undeniable technical, economic and communicative advantages, it is nevertheless a phenomenon tinged with the prospect of unpredictable danger and impending catastrophe. Globalisation is often seen as a powerful means of dividing the world into rich and poor. At present, we lack necessary perceptual tools by which to grasp the fundamental impact of globalisation on our way of life - let alone the tools by which to deal with it. This study goes one step further in that, very much in the spirit of Gebser´s concept of integration, it tracks down new approaches within emerging developments and defines them more precisely in terms of human perception, by way of selected examples. In other words, the study examines the applicability and usefulness of Jean Gebser´s structural models. The result is a firm basis on which to build a deeper understanding of the overall phenomenon of globalisation. This understanding can give rise to a new political mode of action that overcomes the prevailing sense of impotence and helplessness. Heinrich Leopold´s treatise is based on the notion that Kant´s ideal of eternal peace and Aurobindo´s concept of human unity have to be reassessed and redefined in this age of globalisation. In this context, Jean Gebser´s structural model and his descriptions of the integral provide an opportunity for us, in our time, to undertake a sober appraisal of the circumstances while at the same time gainging new insights into the discourse on globalisation.